Up-regulated miR-106b inhibits ox-LDL-induced endothelial cell apoptosis in atherosclerosis - Zhang,Yunqing (2020)
This research aimed to explore the molecular mechanism of microRNA (miR)-106b in cell apoptosis of atherosclerosis (AS). Human aortic endothelial cells (HAECs) were divided into control group, oxidized-low-density lipoproteins (ox-LDL) group, miR-106b NC+ox-LDL group, miR-106b mimics+ox-LDL group, miR-106b mimics+PTEN+ox-LDL group, and miR-106b mimics+empty+ox-LDL group. Real-time fluorescence quantitative polymerase chain reaction, cholecystokinin, TdT-mediated biotinylated nick end-labeling assay, luciferase reporter gene assay, and flow cytometry analysis were performed to determine the morphology, proliferation, and apoptosis in HSECs. Moreover, the levels of phosphatase and tensin homolog deleted on chromosome 10 (PTEN), Bcl-2, p-P13K, and p-AKT in HAECs were detected by western blot. MiR-106b was down-regulated in ox-LDL-induced HAECs. PTEN was the target gene of miR-106b-5p. Overexpression of PTEN inhibited the anti-apoptotic effect of miR-106b. Compared with the control group, the proportion and number of HAECs apoptosis and Bax, caspase-3, and caspase-9 expression in ox-LDL and miR-106b mimics+PTEN+ox-LDL groups were significantly increased (all P<0.05). Moreover, the activity of HAECs and Bcl-2 were decreased significantly (all P<0.05). Overexpression of miR-106b in ox-LDL-induced AS inhibited endothelial cell apoptosis. Furthermore, miR-106b might activate the PI3K/AKT pathway by down-regulating the expression of PTEN in ox-LDL-induced HAECs.